Menu attributes and students’ purchase decision: a case of Tealive / Hazmal Ismail ... [et al.] - Ismail, Hazmal; Abdullah, Dayang Nur Aisyah; Noor Rizian, Awang Tuah Nurain Fatihah; Rasul, Rozaidy; Md Zain, Nur Adilah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
Menu attributes offer the customer convenience and option before the buying decision is made. Therefore, this study was conducted to explore the theory of menu attributes that influence purchasing decisions of Tealive products among students in UiTM Puncak Alam, Selangor. The data for this research is captured from a survey questionnaire that the researcher had developed and distributed to carry off research aims. The data was analyzed with SPSS to assess and identify the menu attributes and students’ purchase decisions. This study found that beverage product, price, and services type have influenced the students of UiTM Puncak Alam to purchase the products offered by Tealive.